Sociological Perspective on Women in "The Lives of Others" - Rahiminezhad, Vida (International Journal of Education and Cognitive Sciences, 2022)
Introduction: The Lives of Others won 2006 Academy Award for best foreign language film. This movie exposes the unlimited potential of human beings; it is a multidimensional movie, which concludes tragedy, political oppression, intrigue, and betrayal. This paper aims to examine lives of women in the light of sociological outlook of gendered subaltern and also the concept of Self and Other in “The Lives of Others”. Materials and Method: The methodology of this study is qualitative library-based. It portrays the life of people in East Berlin in 1984, five years before the fall of Berlin Wall.Results: It is found that this movie is successful in portraying the male citizens’ exploitation, and hardship of their activist’s task, but it marginalizes women and portrays them as those of ignorant gendered subalterns who do not have any voice of themselves and do not know how to use the language which is the tool for maintaining Otherness and protecting the Self.Conclusion: Women are portrayed as others since they are capable of betrayal under pressure and they are deviant as the result of being the only person in the movie to be addicted to drag. On the whole they are those who are not capable of being among decision makers even those men decision makers who are considered as others before Stasi.